Beginning with the End in Mind : Implications for Project Design - Carvalho, Soniya (Taylor and Francis, 2015)
As with other donor agencies, the World Bank uses an objectives-based approach to monitoring and evaluating the effectiveness of projects. When projects run into problems and fail to meet their objectives, experience suggests that many of the problems could have been avoided or mitigated through a more systematic focus, from the outset, on the project’s objectives, the outcomes embedded in those objectives and the associated results framework. This article discusses how to improve the prospects of achieving sustainable outcomes by addressing specific questions from the very start of project design, or, in other words, by beginning with the end in mind.